2020
DOI: 10.3389/fnbeh.2020.587560
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Use and Potential Effectiveness of Physical Activity in Managing Autism Spectrum Disorder

Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by poor social and communication skills. Therapeutic interventions are behavioral and educational-normally delivered as structured programs. Several well-established programs exist and most of them do not incorporate physical activity and exercise as core elements. Deficiencies in motor skills are associated with ASD and physical activity has been shown to reduce maladaptive behaviors with autistics. However, the notion of exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 70 publications
0
10
0
3
Order By: Relevance
“…Therefore, the early detection of motor signs in HR individuals, even when social communication deficits are not evident, represents a relevant warning signal that leads one to suspect the imminent appearance of an ASD clinical picture [ 8 ]. In this perspective, it is probably not by chance that the physical activity seems to be effective not only on motor skills but also on social-communication skills and behavior (see reduction of maladaptive and stereotypical behaviors) in ASD children and adolescents, improving their quality of life [ 77 , 78 ]. Yet, many aspects about early motor dysfunction in ASD still need to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the early detection of motor signs in HR individuals, even when social communication deficits are not evident, represents a relevant warning signal that leads one to suspect the imminent appearance of an ASD clinical picture [ 8 ]. In this perspective, it is probably not by chance that the physical activity seems to be effective not only on motor skills but also on social-communication skills and behavior (see reduction of maladaptive and stereotypical behaviors) in ASD children and adolescents, improving their quality of life [ 77 , 78 ]. Yet, many aspects about early motor dysfunction in ASD still need to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…However, sometimes motor difficulties can limit individuals with ID and ASD to participate in PA. Sefen et al (2020) research on the beneficial use and potential effectiveness of PA in managing ASD suggested that in terms of PA programs and behavior interventions, each person with ASD has a highly individualized set of symptoms and characteristics that require highly individualized plans.…”
Section: Discussionmentioning
confidence: 99%
“…Outro aspecto observado pelos pais positivamente nos participantes é que não existiu um comportamento de aversão quanto a pratica do judô ou um fator negativo em seus filhos quando praticaram o judô, apenas momentos de ansiedade para que a aula ocorresse, com exceção da primeira aula, pois os alunos ficavam ansiosos, o que acaba sendo normal, visto que é uma surpresa e quebra da rotina de vida dos mesmos, e a rotina diária é um fator importante para esses indivíduos (RIVERA, RENZIEHAUSEN, GARCIA, 2020). O programa realizado por Sefen et al, (2020) para estudo com crianças e adolescentes com TEA, foi utilizado o método TEACCH (método onde é realizada uma avaliação para perceber os pontos fortes e de maior interesse assim como suas dificuldades, para a partir disso realizar uma estratégia individualizada); utiliza-se esse tipo de método para o tratamento e educação de crianças autistas e com deficiências relacionadas a comunicação. O estudo mostrou que a atividades físicas como instrumento terapêutico tem seus benefícios para a saúde de crianças e adolescentes com TEA e a importância da relação dos pais nos encontros.…”
Section: Discussionunclassified
“…O autor ainda relata que cada pessoa com essa condição genética tem sintomas e características individualizadas, dando ênfase há uma carência em relação às pesquisas que as envolvam; efeitos de longo prazo com a atividade física se tratando de pessoas com o transtorno no espectro autista faz-se necessário se atentar a individualidade biológica de cada aluno e verificar efeitos crônicos do exercício como terapia para as crianças e adolescentes com o transtorno (SEFEN et al, 2020).…”
Section: Discussionunclassified